Food products quality and nutrition in relation to public. Balancing health and disease: Food safety & hygiene promotion - Aljerf, Loai; Aljerf, Ninar (Progress in Nutrition, 2023)
Foods safety as milk and dairy products are inspected as a dedicated quality management tool and a checkpoint to safeguard by detecting microbes, germs, and other unsafe elements. The inspection service is maintaining compliance and safety which ensures that the products are properly labeled and packaged, and to prevent foodborne diseases as recommended by the Food and Drug Administration (FDA). This article discusses microbial and chemical contaminations in some food products, which helps to enhance the health consciousness that is also important for maintaining industrial food hygiene by raising the awareness of hazards and alertness to danger. Micronutrient content of some underutilized and lesser-known aquatic plants have numerous potential for contributing to the Sustainable Development Goals, particularly in combating micronutrient deficiencies. Trace elements shortages are due to a number of clinical signs.